From Numbers to Profits: How Member Count and Savings Drive Cooperative Success - Azhari, Azhari; Konadi, Win; Sumantri Mangkuwinata, Denny; Yanna, Sri (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Cooperatives as economic organizations based on member participation have an important role in improving the social and economic welfare of the community. However, the main challenge facing cooperatives is how to maximize profitability while still maintaining the basic principles of cooperatives. This study aims to analyze the effect of the number of members and total deposits on cooperative profitability, using the remaining results of operations (SHU) as a performance indicator. The method used in this research is quantitative to examine the relationship between the independent variables, namely the number of members and deposits of cooperative members, while the dependent variable is SHU in cooperatives. The data used is secondary data from the Ministry of Cooperatives of the Republic of Indonesia from 2000 to 2023. The results showed that both the number of members and deposits have a positive and significant influence on the SHU of cooperatives, which indicates the importance of member and deposit management in driving the financial success of cooperatives. The implications of these findings provide insights for cooperative managers to increase member engagement and deposit management efficiency to improve profitability. Separating cooperatives based on their type is of particular interest for future research